2014
DOI: 10.1128/mcb.00135-14
|View full text |Cite
|
Sign up to set email alerts
|

PZR Coordinates Shp2 Noonan and LEOPARD Syndrome Signaling in Zebrafish and Mice

Abstract: g Noonan syndrome (NS) is an autosomal dominant disorder caused by activating mutations in the PTPN11 gene encoding Shp2, which manifests in congenital heart disease, short stature, and facial dysmorphia. The complexity of Shp2 signaling is exemplified by the observation that LEOPARD syndrome (LS) patients possess inactivating PTPN11 mutations yet exhibit similar symptoms to NS. Here, we identify "protein zero-related" (PZR), a transmembrane glycoprotein that interfaces with the extracellular matrix to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…SH2 domain-containing tyrosine phosphatase-2 (SHP2), a ubiquitously expressed nonreceptor PTP containing two Src homology 2 (SH2) domains and one catalytic PTP domain, is encoded by the protein tyrosine phosphatase nonreceptor type 11 (PTPN11) gene (14). Activating mutations in SHP2 underlie the Noonan syndrome that manifests as congenital heart disease, short stature, and facial dysmorphia (15,16). SHP2 regulates activated tyrosine kinase receptors including PDGFR, by binding to and dephosphorylating them (17,18).…”
mentioning
confidence: 99%
“…SH2 domain-containing tyrosine phosphatase-2 (SHP2), a ubiquitously expressed nonreceptor PTP containing two Src homology 2 (SH2) domains and one catalytic PTP domain, is encoded by the protein tyrosine phosphatase nonreceptor type 11 (PTPN11) gene (14). Activating mutations in SHP2 underlie the Noonan syndrome that manifests as congenital heart disease, short stature, and facial dysmorphia (15,16). SHP2 regulates activated tyrosine kinase receptors including PDGFR, by binding to and dephosphorylating them (17,18).…”
mentioning
confidence: 99%
“…*P < 0.05; **P < 0.01; ***P < 0.001. interact directly with the tyrosyl-phosphorylated ITIMs of PZR, resulting in SHP2 activation and initiation of adhesion signaling to ERK1/2 (32). Previously, we demonstrated using a nonbiased differential phosphotyrosyl proteomic screen that PZR is the most hyper-tyrosyl-phosphorylated protein in the hearts of Ptpn11 D61G/+ mice (31). We further showed that the expression of NS-and NSML-associated SHP2 mutants is sufficient to enhance PZR tyrosyl phosphorylation and SHP2 binding (31).…”
Section: Pzr Tyrosyl Phosphorylation In Ns Micementioning
confidence: 86%
“…Previously, we demonstrated using a nonbiased differential phosphotyrosyl proteomic screen that PZR is the most hyper-tyrosyl-phosphorylated protein in the hearts of Ptpn11 D61G/+ mice (31). We further showed that the expression of NS-and NSML-associated SHP2 mutants is sufficient to enhance PZR tyrosyl phosphorylation and SHP2 binding (31). These data suggest that the tyrosine kinase(s) that mediates PZR tyrosyl phosphorylation and subsequently SHP2 binding to PZR may serve as an important driver to promote cardiac dysfunction in both NS and NSML.…”
Section: Pzr Tyrosyl Phosphorylation In Ns Micementioning
confidence: 99%
See 2 more Smart Citations